Parenthood stressfulness and intensity in the students' views - I. V. Tikhonova; Yu. V. Misiyuk; U. Yu. Sevastyanova (Russian State Vocational Pedagogical University, 2023)
Introduction. There is an increase in young people's reproductive decisions in the form of conscious childlessness, deferred parenthood, and small families. The role of reproductive decision-making in the non-optimistic demographic forecast of the state actualizes scientific research factors and conditions for the emergence of childbearing attitudes. Subjective factors, which determine fertile plans, are no less important than the objective ones (material, social). In the subjective picture of potential parenthood, the ideas about a stressful parenting role are of great importance. High demands are made to it and transmitted at the level of public expectations. This forms intensive education practice and a stable attitude towards the perception of fatherhood and motherhood long before the children's birth.Aim. The present research aims to study the peculiarities of student ideas about the stressfulness and parental role intensity in the gender factor context and reproductive plans.Methodology and research methods. The sample consisted of 364 childless students (M = 19.43 years). To achieve a study goal, the sample was divided by gender (218 girls and 146 boys) and by orientation towards having children: childlessness (n = 32); large families (n = 75); having few children (n = 257). The following methods and techniques were used: authors' questionnaire; methodology "Parental Stress Scale" by J. O. Berry & W. H. Jones (1995) in the adaptation of Yu. V. Misiyuk, I. V. Tikhonova (2022); "Intensive Parenting Attitudes Questionnaire" by M. Liss, H. H. Schiffrin, V. H. Mackintosh, H. Miles-McLean, M. J. Erchull (2013) in the adaptation of Yu. V. Misiyuk (2022); the authors' version of a semi-structured interview, which studies the ideas of young people about the stressors of parental life in different periods of child development and stress intensity. The methods of statistical processing were employed.Results. The authors revealed stressfulness specificity and parental stress intensity, their content depending on the orientation towards childbearing and gender roles. Child-free students associate parenthood with a high level of parental stress. It is unsatisfying, lacks resources, threatens to lose control over one's own life, and makes high demands on the necessity to stimulate children's development. Students oriented on having many children demonstrate a balanced view on parenthood stressfulness in terms of resources and costs. Students, focused on having few children, have an idea of moderate parental stressfulness. They point to such possible signs of parental stress as "loss of control" and "parental stressors".Girls assess a parental stressfulness role higher than boys; they expect a lower satisfaction level, a high stress level during the periods of early and preschool child development. Girls demonstrate the severity of attitudes towards essentialism, and young men towards child-centrism. The essentialisation of parenthood strengthens the ideas about parenthood stressfulness, whereas the attitude towards getting pleasure from parenthood can be a protection factor.Scientific novelty. For the first time, the characteristics of the stress of the parental role and attitudes towards intensive parenthood in the representations of students are studied. Their interrelation is investigated. The presented results reveal the peculiarities of the perception of the tension of the parental role, its saturation with stress factors, taking into account gender and orientation to childbearing.Practical significance. The research outcomes contribute to the understanding of the patterns and factors of the formation of ideas about the stress of parenthood, its role in the reproductive plans of students. Also, the research results can be used in educational organisations to justify education programmes on parenting and psychological support.